PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK - Kusuma Wijayanto (Universitas Muhammadiyah Surakarta, 2015)
This research was generally aims to analyze the influence of service quality on customer satisfaction which consists of tangible dimension, reliability, responsiveness, assurance and empathy towards customer satisfaction and loyalty. Special purpose of this study were: 1) To analyze Effect tangible dimension, reliability, responsivenenss, assurance, and empathy towards customer satisfaction at Bank Jateng Syariah Cabang Surakarta. 2) know how far the customer satisfaction in influencing customer loyalty Bank Jateng Syariah Cabang Surakarta, the sample used in this research was sum to 100 respondents, the sampling technique by using accidental sampling. Methods of data analysis used is multiple linear regression statistical test while using the t test and F test and test-R2. The results of this research showed tangible dimension of service quality, reliability, responsivenenss, assurance, and empathy together influence on customer satisfaction. Whereas customer satisfaction variable also affect customer loyalty.